Rates of chronic absenteeism in Montessori and non-Montessori Title 1 schools - LeBoeuf, Lee; Goldstein-Greenwood, Jacob; Lillard, Angeline S. (Frontiers in Education, 2023)
In this study, we asked whether Montessori schools, which tend to have high student engagement, are associated with lower average rates of chronic absenteeism and/or smaller racial disparities therein relative to non-Montessori schools. We use multilevel modeling to answer this question, following an approach proposed in Author et al., (in press) for analyzing racial disparities in count outcomes. We identified a sample of Title 1 Montessori and non-Montessori schools using propensity score matching and data from the Civil Rights Data Collection. We did not observe significant differences in average overall rates of chronic absenteeism across school types, nor in average racial disparities in the rates of chronic absenteeism between Black and White or Hispanic and White students, though Montessori schools had slightly lower average rates for White students. We discuss shortcomings in the way chronic absenteeism data is collected, and how these shortcomings do not allow researchers to answer questions about why students are chronically absent, thereby limiting intervention work.